Plan for the Sustainability of Public Buildings through the Energy Efficiency Certification System: Case Study of Public Sports Facilities, Korea - Seon Gyeong Baek (Buildings, 2021)
This study examines strategies for energy efficiency in public buildings in Korea and the implementation of certification systems. It also identifies the actual plan status and discusses improvements at the institutional level. The target is the national sports centers, where the discussion on energy efficiency has been assiduous, as they have recently expanded regionally in Korea. Among the 541 national sports centers in Korea, 90 facilities for which a preliminary review was performed on the plan by the National Public Building Center were analyzed. The energy efficiency plan is realized through Building Energy Efficiency, Zero Energy Building, and Green Standard for Energy and Environmental Design certifications. As a result of analyzing the plan status, omissions or errors in certification were confirmed in about 10% of each, even though more than 80% of the facilities were subject to mandatory application. In Korea’s condition, to revitalize the practice of the system, it is necessary to expand the government’s publicity and support initiatives, use differential application of evaluation items, and strengthen incentives. This study provides meaningful results and suggestions for implementing an energy efficiency system at the national level under similar conditions in the future.